One-pot, multicomponent synthesis of symmetrical Hantzsch 1,4-dihydropyridine derivatives using glycerol as clean and green solvent - Sohal, Harvinder Singh; Goyal, Arun; Sharma, Rajeev; Khare, Rajshree (European Journal of Chemistry, 2014)
Multi component, one pot synthesis of symmetrical 1,4-dihydropyridine derivatives from the condensation of ethyl/methyl acetoacetate, aromatic/aliphatic aldehyde and ammonium acetate has been described using glycerol, as economical, easily available and environmentally benign reagent. The targeted molecules were obtained in high purity and excellent yield without use of any additional catalyst and methodology from readily available starting materials.